PISA Problem-Solving of Students’ Mathematical Literacy in Adversity Quotient Perspective - Lestari, Dea Ayu; Prayitno, Lydia Lia (Universitas Negeri Surabaya, 2025)
This descriptive qualitative study selected three high school students to describe students' mathematical literacy skills in solving PISA model problems based on adversity quotient (AQ). Three subjects from different AQs were involved in this study based on the results of completing the Adversity Response Profile (ARP) questionnaire and good oral communication skills based on the advice of mathematics teachers. Students' AQ was collected through ARP questionnaire instrument, mathematical literacy skills were collected through providing PISA questions and interview guidelines. Furthermore, the data were analyzed based on the stages of reduction, presentation, and conclusion. The results of completing the ARP questionnaire obtained three subjects with AQ climber, camper, and quitter supported by good communication skills. The results of this study and through triangulation of techniques showed that subjects with AQ climber and camper satisfied five indicators of mathematical literacy skills, including communication, mathematization, reasoning and argumentation, using mathematical tools, and designing solution strategies. Meanwhile, AQ quitter subjects were only able to satisfy four indicators of mathematical literacy indicators, which are mathematization, representation, reasoning and argumentation, use of mathematical tools, and design of solution strategies. The findings of this study are that quitter subjects are unable to satisfy communication indicators while climber and camper subjects are able to satisfy communication indicators. In addition, quitter subjects were also unable to use symbolic, technical, formal, language and operation forms in solving PISA problems, while climber and camper subjects were able to satisfy these indicators.